PELATIHAN PENATAAN ARSIP AKTIF DAN ARSIP INAKTIF PADA PERANGKAT DESA SENDUK KECAMATAN TOMBARIRI KABUPATEN MINAHASA - Jufrina Mandulangi; Deky E. Wibowo Mundung (JURNAL DAYA-MAS, 2023)
The role of archives is very important for an organizational institution because archives as a source of information for memory centers cause archives to be managed properly so that if they need it, archives can be presented quickly and precisely. In Law Number 43 of 2009, Chapter 1 article 1 paragraph 3 to paragraph 9 there are active archives, where the frequency of use is high and / or continuous, whereas inactive archives are archives whose frequency of use has decreased. So far, there are still village officials who view the problem of active and inactive archives as trivial, and do not need to be followed up. The Senduk village apparatus, Tombariri District, Minahasa Regency will be used as a partner to solve this problem that he often experiences. This view results in poor ways of organizing and storing archives. This poor storage greatly affects the loss and damage to village archives or documents so that the effectiveness of services to the community does not work well. To change the paradigm of thinking that archives are absolutely necessary, the solution offered to solve the problem is in the form of training on the administration of active and inactive archives in village devices. This training is one of the methods carried out in PIM activities as an effort to increase awareness and skills in dealing with this situation considering that village officials are considered to need to get a positive impact from the existence of local government services. The purpose of this activity is to provide guidance on the administrative management of archive arrangement in the archive storage system.